The Impact of Cash Flow and Sales Volatility and Deferred Tax Expense on Earnings Persistence with Financial Leverage as a Moderating Variable in Property and Real Estate Sector Companies on the IDX (2021-2023) - Kurnia, Putri Puji; Riswan, Riswan (LPPPIPublishing, 2025)
This study aims to analyze the impact of operating cash flow volatility (Cash Flow Volatility), sales volatility (Sales Volatility), and deferred tax expense (Deferred Tax Expense) on earnings persistence in property and real estate sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2021-2023, with financial leverage as a moderating variable. The method used is multiple linear regression with a moderation test to test the direct and moderating effects of leverage on the relationship between variables. The results of the study indicate that sales volatility (Sales Volatility) has a significant negative effect on earnings persistence, while deferred tax expense (Deferred Tax Expense) has a significant positive effect. On the other hand, operating cash flow volatility (Cash Flow Volatility) does not show a significant effect. Although the moderating variable (leverage) does not directly moderate the relationship between the independent variables and earnings persistence, the presence of leverage strengthens the overall regression model, as evidenced by the increase in the R² value from 53.8% to 58.5%. This study provides insights into the importance of managing cash flow and sales volatility and the impact of deferred tax expense on corporate earnings performance, as well as the importance of taking leverage into account in improving the predictive power of financial models.